Service Quality Influencing Patient Satisfaction at Luang Prabang Provincial Hospital - kanmany, vone; Keoboualapheth, Soulideth; Silivanh, Sommay (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
The objective of this research were to study 1) the attitude of the patient toward service quality at the Luang Prabang provincial Hospital, and 2) The service quality influencing patient satisfaction at Luang Prabang Provincial Hospital. The participants of this study were 385 patients; these covered the patient and their relatives who received services at the Luang Prabang provincial Hospital. The research used the questionnaire as a tool to collect data. Data were analyzed by calculating mean, standard deviation, analyze the relationship of variables and analyze the multiple regression. The findings indicated that 1) the attitude of the patient toward service quality at the Luang Prabang provincial Hospital found that a high level such as well diagnosis, well convenience, well and quick treatment, well cleanness, for the well hospitality was a median level. 2) The service quality well cleanliness factor, well convenience, and well and quick treatment influencing patient satisfaction at Luang Prabang Provincial Hospital.